Glial metabotropic glutamate receptor-4 increases maturation and survival of oligodendrocytes - Spampinato, Simona F.; Merlo, Sara; Chisari, Mariangela; Nicoletti, Ferdinando; Sortino, Maria Angela (Frontiers in Cellular Neuroscience, 2015)
Group III metabotropic glutamate (mGlu) receptors mediate important neuroprotective and anti-inflammatory effects. Stimulation of mGlu4 receptor reduces neuroinflammation in a mouse model of experimental autoimmune encephalomyelitis (EAE) whereas mGlu4 knockout mice display exacerbated EAE clinical scores. We now show that mGlu4 receptors are expressed in oligodendrocytes, astrocytes and microglia in culture. Oligodendrocytes express mGlu4 receptors only at early stages of maturation (O4 positive), but not when more differentiated (MBP positive). Treatment of immature oligodendrocytes with the mGlu4 receptor agonist L-AP4 (50 μM for 48 h) accelerates differentiation with enhanced branching and earlier appearance of MBP staining. Oligodendrocyte death induced by exposure to 1 mM kainic acid for 24 h is significantly reduced by a 30-min pretreatment with L-AP4 (50 μM), an effect observed only in the presence of astrocytes, mimicked by the specific mGlu4 receptor positive allosteric modulator PHCCC (30 μM) and prevented by pretreatment with the mGlu4 receptor antagonist, CPPG (100 μM). In astrocytes, mGlu4 receptor is the most expressed among group III mGlu receptors, as by QRT-PCR, and its silencing prevents protective effects. Protection is also observed when conditioned medium from L-AP4-pretreated astrocytes is transferred to oligodendrocytes challenged with kainic acid. Transforming growth factor β (TGF-β) mediates the increased oligodendrocyte survival as the effect of L-AP4 is mimicked by addition of 10 ng/ml TGF-β and prevented by incubation with a neutralizing anti-TGF-β antibody. In contrast, despite the expression of mGlu4 receptor in resting and activated microglia, conditioned medium from L-AP4-stimulated microglia does not modify kainate-induced oligodendrocyte toxicity. Our results suggest that mGlu4 receptors expressed in astrocytes mediate enhanced survival of oligodendrocytes under conditions of excitotoxicity.